SAT0317 HDL-CHOLESTEROL EFFLUX CAPACITY IS DOWNREGULATED IN PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - Ferraz-Amaro, I.; Esmeralda, D. F.; Hernández-Hernández, V.; Sánchez-Pérez, H.; De Armas-Rillo, L.; Armas González, E.; Machado, J. D.; Díaz-González, F.
Abstract : Background: It is well established that patients with systemic sclerosis (SS) show a disrupted lipid profile and an increased cardiovascular risk. Cholesterol efflux capacity (CEC) is the ability of high-density lipoprotein (HDL)-cholesterol to accept cholesterol from macrophages. CEC has been linked to cardiovascular events in the general population and to subclinical atherosclerosis in patients with rheumatoid arthritis and systemic lupus erythematosus. Objectives: The main purpose of our study was to assess, for the first time, whether CEC is disrupted in patients with SS compared to controls. We also aimed to identify patients' characteristics that could explain such potential CEC disturbance. Methods: Cross-sectional study that encompassed 188 individuals; 73 SS patients and 115 age- and sex-matched controls. CEC, using an in vitro assay, and lipoprotein serum concentrations were assessed in patients and controls. A multivariable analysis was performed to study the differences in CEC between patients and controls, and if SS-related data could explain CEC differences. Results: CEC was downregulated in SS patients as compared to controls (beta coefficient -6 [95%CI -10- -2] %, p=0.002). This occurred independently of traditional cardiovascular risk factors, statin use or other variations in the lipid profile produced by the disease. Demographics and lipid profile were, in general, not related with CEC in both patients and controls. In this sense, only abdominal circumference showed a positive association with CEC in patients (beta coefficient 0.09 [95%CI 0.03-0.14], p=0.002) but not in controls. Similarly, no traditional cardiovascular risk factors were related with CEC in both populations. Regarding lipid profile, no correlations were identified between the standard lipid profile molecules and CEC. Remarkably, the use of statins was not related to CEC in both patients and controls. Lastly, concerning SS related data, a negative association between mRSS and CEC was identified (beta coef. -1.08 [95%CI -2.03- -0.12] %, p=0.028). Skin thickness through modified Rodnan (mRSS) was positively related to age and the presence of hypertension, but negatively associated with apolipoprotein B, apo B:A1 ratio, and CEC when univariate correlations were assessed (Table 4). When the relation of mRSS to these lipid-related molecules was adjusted for traditional CV risk factors, the statistical significance of mRSS with those molecules was maintained. Moreover, when the relation between mRSS and CEC was additionally adjusted for other lipid-related molecules, its significance was conserved (beta coef. -1.35 [95%CI -2.62- -0.08]) %, p=0.038) Conclusion: CEC is downregulated in SS patients independently of other inflammation-related lipid profile modifications that occur in the disease. Skin thickness is independent and inversely associated with CEC in SS patients. Disclosure of Interests: Iván Ferraz-Amaro Grant/research support from: Pfizer, Abbvie, Speakers bureau: Pfizer, Abbvie, MSD., delgado frias esmeralda Speakers bureau: Pfizer, Abbvie, MSD, Vanessa Hernández-Hernández Speakers bureau: Pfizer, Abbvie, MSD, Hiurma Sánchez-Pérez: None declared, Laura de Armas-Rillo: None declared, Estefania Armas González: None declared, Jose David Machado: None declared, Federico Díaz-González Grant/research support from: Abbvie, Pfizer, MSD, Speakers bureau: Abbvie, Pfizer, MSD